Evaluation of engineering properties of soil for sustainable urban development - Qaysi Saleh; Al-Shmrani Awad; Abdelrahman Kamal (Open Geosciences)
Rapid urbanization in southern Saudi Arabia necessitates accurate geotechnical assessments to support sustainable development. However, the region lacks comprehensive seismic-based soil classification studies, raising concerns regarding construction safety. This study utilizes seismic refraction and tomography techniques to characterize soil properties and evaluate their appropriateness for infrastructure development. Ten seismic refraction and tomography surveys and two multichannel analysis of surface wave profiles were conducted to classify soil conditions based on seismic velocities and geotechnical parameters. The results reveal three distinct subsurface layers: (1) alluvial soil (V p = 300–940 m/s), (2) fractured basement (V p = 1,350–1,890 m/s), and (3) massive basement (V p > 2,400 m/s). According to National Earthquake Hazards Reduction Program criteria, soil classification identifies loose sediments (Class E) as unsuitable for construction, while stiffer deposits (Classes D and C) offer stable foundations. Integrating seismic techniques presents a cost-effective alternative to traditional drilling, providing a rapid assessment tool for urban planners. These findings aid in optimizing construction site selection, thereby minimizing risks associated with weak soil zones.